Effect of HPHT processing on the structure, and thermoelectric properties of Co4Sb12 co-doped with Te and Sn. Issue 8 (27th January 2015) - Sun, Hairui; Jia, Xiaopeng; Deng, Le; Lv, Pin; Guo, Xin; Zhang, Yuewen; Sun, Bing; Liu, Binwu; Ma, Hongan
Abstract : Te–Sn co-doped Co4 Sb12 bulk polycrystalline materials Co4 Sb11.7− x Te x Sn0.3 have been prepared using a high pressure and high temperature method and then characterized using X-ray diffraction. Abstract : Te–Sn co-doped Co4 Sb12 bulk polycrystalline materials Co4 Sb11.7− x Te x Sn0.3 have been prepared using a high pressure and high temperature method and then characterized using X-ray diffraction. The aim was to use the disorder of the lattice orientation generated by both high pressure and doping with Te and Sn to reduce the thermal conductivity. The thermoelectric properties were measured at room temperature. As expected, as the synthesis pressure increased, the Seebeck coefficient and electrical resistivity increased, but the thermal conductivity decreased greatly. A minimum thermal conductivity of 2.41 W m −1 K −1 was obtained at room temperature for Co4 Sb11 Te0.7 Sn0.3 synthesized at 3 GPa.